Toward New Therapeutic Mechanisms in Bipolar Disorder: Analog Investigation of Self-Compassion and Nonattachment to Self - Yang, Yan; Fletcher, Kathryn; Whitehead, Richard; Murray, Greg (Frontiers in Psychology, 2018)
There is growing interest in psychological processes that might be targeted in treatments for bipolar disorder (BD). One such process is a vulnerability at the level of self-concept, characterised by presence of, and fluctuations between positive and negative self-concept. The aim of the present study was to advance this literature by investigating the role of two emerging meta-cognitive processes - self-compassion and nonattachment to self - which have potential to therapeutically modulate this unstable self-concept in BD. Using an analogue design, it was hypothesised that both variables would mediate the relationship between bipolar tendencies and psychological distress in a general population sample. Participants (N = 372 Australian university students) completed self-report measures of manic and depressive tendencies, self-compassion, nonattachment to self and psychological distress. To investigate the specificity of the two hypothesised mediators, a better-researched psychological variable – rumination – was also included in mediation analyses. Bivariate analyses found tendencies towards mania and depression to be associated with diminished self-compassion and nonattachment to self, while both psychological processes were negatively associated with psychological distress. Mediation analyses showed, as expected, self-compassion and nonattachment to self mediated the relationship between bipolar tendencies and psychological distress after controlling for the effects of rumination. The present findings add incrementally to this literature by demonstrating that two meta-cognitive processes – self-compassion and nonattachment to self – act as mediators, and may be modifiable mechanisms linking bipolar vulnerability to negative mood outcomes. Future research should tackle longstanding conceptual issues in this domain, including the relationship between contents of self-concept (an established focus of BD research) and the person’s meta-cognitive approach to their self-concept (the focus here).